2022
DOI: 10.1177/10790632211070799
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Attitudes Towards Individuals with Sexual Convictions on Professional and Student Risk Judgments

Abstract: Attitudes towards individuals with sexual convictions is an area with growing research interest, but the effects of such attitudes on professional judgments is largely unexplored. What is known from the existing literature is that attitudes guide the interpretation of sexual crime related information, which cascade into potential biased or heuristically driven judgments. In this study we recruited samples of both students ( n = 341) and forensic professionals ( n = 186) to explore whether attitudes towards ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Although the current sample differs from both the general population and those working in the criminal justice system, it is unlikely that these differences would meaningfully impact the results. A recent study has found that the relationship between the attitudes toward sexual offenders and risk perception was similar among students and forensic professionals (Harper & Hicks, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although the current sample differs from both the general population and those working in the criminal justice system, it is unlikely that these differences would meaningfully impact the results. A recent study has found that the relationship between the attitudes toward sexual offenders and risk perception was similar among students and forensic professionals (Harper & Hicks, 2022).…”
Section: Discussionmentioning
confidence: 99%